Evaluation of antimycobacterial, leishmanicidal and antibacterial activity of three medicinal orchids of Arunachal Pradesh, India - Manisha Bhatnagar; Nandan Sarkar; Nigam Gandharv; Ona Apang; Sarman Singh; Sabari Ghosal (BMC, 2017)
Abstract Background The ethnic population of Arunachal Pradesh uses a number of orchids as such, or in decoction for various ailments. Three untapped orchids namely, Rhynchostylis retusa, Tropidia curculioides and Satyrium nepalense, traditionally used in tuberculosis, asthma and cold stage of malaria in folk medicine, were selected for the present study. Methods Dried material of each plant was divided into three parts. Solvent extraction and fractionation afforded altogether 30 extracts and fractions, which were evaluated against Mycobacterium tuberculosis (H37Rv and MDR strain) for antimycobacterial activity; promastigotes and amastigotes of Leishmania donovani for leishmanicidal activity and two gram positive and three gram negative clinical isolates for antibacterial activity. Results The most significant antimycobacterial activity was observed with n-hexane fraction of the flower of Satyrium nepalense with MIC of 15.7 μg/mL. The most promising leishmanicidal activity was observed with diethyl ether fraction of the roots of Rhynchostylis retusa with IC50 values of 56.04 and 18.4 μg/mL against promastigotes and intracellular amastigotes respectively. Evaluation of antibacterial activity identified S. nepalense flower n-hexane and R. retusa roots diethyl ether as potential fractions with MIC values of ≤100 μg/mL against selected clinical isolates. Conclusions This is the first report of the plants possessing antimycobacterial and leishmanicidal activity. The investigation resulted in identification of S. nepalense as the most promising plant, which possessed all three activities in significant proportion. This laboratory outcome could be translated to marketable pharmaceutical products and also to produce maximum benefits to the local of nearby area. Graphical abstract Antimycobacterial and leishmanicidal activity of medicinal orchids